Answer:
translation 3 units to the left
Explanation:
The formula for horizontal and vertical shifts is: y = a(x - h)² + k
- "h" is for your horizontal shift
- "k" is for your vertical shift
In this equation a horizontal shift was used because our "h" value went from 0 to +3, meaning our h must be -3
- A negative "h" means there is a translation to the left, towards the negative numbers
- A positive "h" means there is a translation to the right, towards the positive numbers
Plugging this in we get
- y = -3(x - (-3))² + 0 → y = -3(x + 3)²